Ruthenium Stilbenyl and Diruthenium Distyrylethene Complexes: Aspects of Electron Delocalization and Electrocatalyzed Isomerization of the Z-Isomer - Linseis, Michael; Zalis, Stanislav; Zabel, Manfred; Winter, Rainer F. (Journal of the American Chemical Society, 2012)
Regio- and stereoselective insertion of the terminal ethynyl functions of 4-ethynylstilbene, the E and Z isomers of 4,4'-bis(ethynylphenyl)ethene and a backbone-rigidified cyclohexenyl derivative of the Z. isomer into the Ru-H bond of the complex RuClH(CO)((PPr3)-Pr-i)(2) provides the corresponding vinyl ruthenium complexes, which have been characterized spectroscopically and by X-ray crystallography. Large red shifts of the UV/vis absorption bands evidence efficient incorporation of the vinyl metal subunit(s) into the conjugated pi-system. All complexes oxidize at low potentials. The various oxidized forms of all complexes were generated and characterized by UV/vis/NIR, IR and EPR spectroscopies. These studies indicated electrocatalytic Z -> E isomerization of the oxidized Z-distyrylethene complex Ru-Z2, which is prevented in its backbone-rigidified derivative Ru-Z2fix. The radical cations of the E and the configurationally stable cyclohexene-bridged Z-derivatives are spin-delocalized on the EPR time scale but charge-localized on the faster IR time scale. The degree of ground-state charge delocalization in the mixed-valent state has been quantified by the incremental shifts of the Ru-CO bands upon stepwise oxidation to the radical cations and the dications and was found to be remarkably large (19% and 9%) considering redox splittings Delta E-1/2 of just 49 or 74 mV. Quantum chemical studies with various levels of sophistication reproduce our experimental results including the electronic spectra of the neutral complexes and the intrinsically localized nature of the radical cations of the dinuclear complexes.